2021
DOI: 10.3389/fmars.2021.704134
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Patterns of Elemental Tracers in the Vertebrae Cartilage of Coastal and Oceanic Sharks

Abstract: As predators, coastal and oceanic sharks play critical roles in shaping ecosystem structure and function, but most shark species are highly susceptible to population declines. Effective management of vulnerable shark populations requires knowledge of species-specific movement and habitat use patterns. Since sharks are often highly mobile and long-lived, tracking their habitat use patterns over large spatiotemporal scales is challenging. However, the analysis of elemental tracers in vertebral cartilage can desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 83 publications
6
22
4
Order By: Relevance
“…Mn and Li concentrations were also effective at discriminating ABFT between Atlantic and Mediterranean regions with higher concentrations in tunas collected in the Mediterranean waters. Despite the importance of Mn and Li in this study, the relationship between the environmental concentrations of these elements and their incorporation into calcified structures remains inconsistent across species and environments (e.g., Bath Martin and Thorrold 2005 ; Miller 2009 ; Sturrock et al., 2015 ; Mohan et al., 2018 ; Reis-Santos et al., 2018 ; Livernois et al., 2021 ; Martino et al., 2021 ). In addition, experimental studies did not find any evidence of a relationship between seawater Mn and Mn in otoliths (see review by Miller, 2009 ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Mn and Li concentrations were also effective at discriminating ABFT between Atlantic and Mediterranean regions with higher concentrations in tunas collected in the Mediterranean waters. Despite the importance of Mn and Li in this study, the relationship between the environmental concentrations of these elements and their incorporation into calcified structures remains inconsistent across species and environments (e.g., Bath Martin and Thorrold 2005 ; Miller 2009 ; Sturrock et al., 2015 ; Mohan et al., 2018 ; Reis-Santos et al., 2018 ; Livernois et al., 2021 ; Martino et al., 2021 ). In addition, experimental studies did not find any evidence of a relationship between seawater Mn and Mn in otoliths (see review by Miller, 2009 ).…”
Section: Discussionmentioning
confidence: 89%
“…Sr and Ba were unexpectedly less effective than other elements at discriminating specimens between regions. Sr and Ba uptake in otoliths and fin rays is considered to be an environmental proxy for salinity ( McMillan et al., 2017 ; Livernois et al., 2021 ), and has therefore been used to reconstruct fish migrations across salinity gradients (e.g., Elsdon et al., 2008 ; Allen et al., 2009 ; Avigliano and Volpedo 2013 ; Izzo et al., 2018 ; Rogers et al., 2019 ). In elasmobranch vertebrae, while Sr increases Ba decreases with increasing salinity ( Dorval et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trace elements deposited in mineralized vertebral cartilage provide additional life history information as environmental tracers (McMillan et al, 2017;Livernois et al, 2021). Controlled laboratory experiments with model elasmobranch species have demonstrated that temperature and dissolved water chemistry affect uptake of barium (Ba:Ca) in round stingrays Urobatis halleri (Smith et al, 2013) and temperature influences manganese (Mn:Ca), strontium (Sr:Ca), and Ba:Ca uptake in Port Jackson sharks (Heterodontus portusjacksoni) (Pistevos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%